2021
DOI: 10.7769/gesec.v12i1.1150
|View full text |Cite
|
Sign up to set email alerts
|

Intenção empreendedora e a influência das teorias do comportamento planejado e dos valores humanos

Abstract: Os empreendedores destacam-se como agentes de fortalecimento das economias locais pelo seu poder de promover o crescimento econômico ligado aos seus negócios. Investigar a formação da Intenção Empreendedora (IE) é determinante para o entendimento do processo de empreendedorismo. Baseando-se na Teoria do Comportamento Planejado (TCP) de Ajzen (1991) e na Teoria dos Valores Humanos de Schwartz (2001), este trabalho objetivou identificar a influência do comportamento planejado e dos valores humanos na IE de estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(48 reference statements)
1
5
0
1
Order By: Relevance
“…Both works of Martins, Serralvo and João (2014), based on the Theory of Planned Behavior (TPB) as a model used in Psychology (and other areas) with the objective of demonstrating and anticipating various behaviors of individuals, as well as the results of meta-analysis carried out by Schlaegel and Koening (2014) and Liñán and Fayolle (2015), which allowed the identification of the theoretical framework of studies on entrepreneurial intention, evidenced the prevalence of TPB (Ajzen, 1991), a proposal taken as a model in this study. Similar indications were also presented by Marcon, Silveira and Frizon (2021).…”
Section: Entrepreneurial Intentionsupporting
confidence: 85%
“…Both works of Martins, Serralvo and João (2014), based on the Theory of Planned Behavior (TPB) as a model used in Psychology (and other areas) with the objective of demonstrating and anticipating various behaviors of individuals, as well as the results of meta-analysis carried out by Schlaegel and Koening (2014) and Liñán and Fayolle (2015), which allowed the identification of the theoretical framework of studies on entrepreneurial intention, evidenced the prevalence of TPB (Ajzen, 1991), a proposal taken as a model in this study. Similar indications were also presented by Marcon, Silveira and Frizon (2021).…”
Section: Entrepreneurial Intentionsupporting
confidence: 85%
“…In this logic, studies [10,26] found that personal attitudes positively influence the entrepreneurial intentions of university students. Accordingly, Choudhury and Mandal [21] (pp.…”
Section: Relationship Between Contextual and Individual Factorsmentioning
confidence: 99%
“…Knowing the contextual antecedents of the individual factors formed by the Theory of Planned Behavior [9] helps undergraduate courses, to develop pedagogical proposals and learning strategies that foster the sustainability of business activities and a culture of student sustainability [8][9][10]26].…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura recente, esse instrumento de coleta de dados tem sido utilizado em diferentes realidades (Martins et al, 2019). No Brasil, grande parte das pesquisas que utilizaram estudantes universitários como amostra empregou o QIE para a coleta dos dados (Marcon et al, 2021;Marcon et al, 2020;Paiva et al, 2020;Sousa et al, 2020Krueger et al, 2019Hecke, 2011). A padronização dos instrumentos de medição é o que permite que diferentes pesquisas sejam comparadas (Sousa et al, 2020;Marcon et al, 2020;Paiva et al, 2020;Krüger et al 2019;Ferreira et al, 2017;Camozzato et al, 2018;Birchler & Teixeira, 2017;Oliveira & Leal 2015;Zhang et al, 2015;Liñán et al, 2011;Liñán & Chen, 2009;Krueger et al, 2000).…”
Section: Referencial Teóricounclassified